The Effectiveness of Group Counseling Program Based on Dialectical Behavior Therapy in Reducing Impulsive and Disruptive Behaviors Among Tenth Grade Female Students - Abueita , Siham; Al Shamayleh, Alaa (Jordan Journal of Educational Sciences, 2017)
This study aimed to verify the effectiveness of group counseling program, based on dialectical behavior therapy in reducing impulsive and disruptive behaviors among tenth grade female students .The sample of study consisted of (29) females students from two secondary schools for girls in Zarka Governorate، they were purposely selected, but randomly distributed into two groups: An experimental group (N=14) students, and a control group (N =15) students. The impulsive and destructive behavior scales were developed and the validity and reliability verified. The counseling program was developed based on dialectical behavior therapy skills; mindfulness, emotional bonding regulation, tolerance, and interpersonal effectiveness, it consisted of (15) sessions, and was applied to the experimental group. The results revealed statistically signisicant differences between the experimental group and the control group in reducing impulsive and disruptive behaviors, in favor of the experimental group, and between the post and fellow up test on the experimental group in favor of fellow up test